2019
DOI: 10.3390/biom9060229
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Leucine-Rich Diet Minimises Muscle Mass Loss in Tumour-bearing Adult Rat Offspring by Improving the Balance of Muscle Protein Synthesis and Degradation

Abstract: Cachexia syndrome can affect cancer patients and new prevention strategies are required. Maternal nutritional supplementation can modify metabolic programming in the offspring, which lasts until adulthood. This could be a good approach against diseases such as cancer. A 3% leucine-rich diet treatment improved muscle protein turnover by modifying the mTOR and proteolytic pathways, thus we analysed whether maternal supplementation could ameliorate muscle protein turnover in adult offspring tumour-bearing rats. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 44 publications
(61 reference statements)
7
10
0
Order By: Relevance
“…Intense body weight loss is expected during cancer cachexia, as verified in the AW animals in this study, and similar to others’ results for this same tumour model [ 27 , 28 , 29 ]. The tumour also affected the body growth and development in WW animals, but to a lesser extent, probably because this group was still in the growing phase.…”
Section: Discussionsupporting
confidence: 93%
“…Intense body weight loss is expected during cancer cachexia, as verified in the AW animals in this study, and similar to others’ results for this same tumour model [ 27 , 28 , 29 ]. The tumour also affected the body growth and development in WW animals, but to a lesser extent, probably because this group was still in the growing phase.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, strategies to prevent this condition are required. In this way, our previous study showed a maternal diet supplementation as a preventive approach against muscle wasting in an experimental model of cancer cachexia [3]. Based on leucine ability to cross the placental barrier and to modify the milk composition leading to epigenetics marks on the offspring [4][5][6], our study demonstrated that a leucine-rich diet when maternally administered diminished the muscle mass loss in adult offspring tumor-bearing rats.…”
Section: Introductionmentioning
confidence: 56%
“…Based on leucine ability to cross the placental barrier and to modify the milk composition leading to epigenetics marks on the offspring [4][5][6], our study demonstrated that a leucine-rich diet when maternally administered diminished the muscle mass loss in adult offspring tumor-bearing rats. This approach reduced the cachexia negative protein balance, which ameliorated the gastrocnemius muscle protein synthesis and decreased protein degradation, by activating the mechanistic target of rapamycin (mTOR) pathway and maintaining muscle cathepsin H and calpain activities [3].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, other protein degradation pathways could be driving this spoliation, as seen in previous studies with the same tumor model. [39,40] Moreover, it would be interesting to evaluate the proteasomal activity correlating with the proteasomal protein expression levels. This analysis could also be important to clarify the maternal influence over this degradation pathway, which is a limitation of our study.…”
Section: Discussionmentioning
confidence: 99%